Bentuk Pengaturan Undang-Undang Sistem Peradilan Anak Khusus Untuk Anak Di Bawah Umur Sebagai Pelaku Residivis Tindak Pidana Curanmor - Putri Rahayu Ismail; Moh R U Puluhulawa; Mohamad Taufiq Zulfikar Sarson (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This journal examines the form of legal regulation related to the juvenile justice system in Indonesia, with a special focus on minors who are recidivists of the crime of motor vehicle theft (curanmor). Even though Law no. 11 of 2012 concerning the Juvenile Criminal Justice System has comprehensively regulated the handling of children in conflict with the law. There are significant challenges in handling children who repeatedly commit criminal acts. This study uses a normative juridical approach with analysis of applicable laws and regulations as well as cases of recidivism among children who commit crime. The research results show that although the law has provided a framework for the protection and rehabilitation of children, its implementation is often not optimal, especially in handling recidivist children. Special policies are needed that are more focused on preventing recidivism, including strengthening the role of rehabilitation institutions and active involvement of families and communities. In addition, revision of several provisions in existing laws is needed to ensure that the handling of recidivist children can be more effective and fair.